Radio and the rise of Nazi in pre-war Germany - Maja Adena; Ruben Enikolopov; Maria Petrova; Veronica Santarosa; Ekaterina Zhuravskaya (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
How far can media undermine democratic institutions and how persuasive can it be in assuring public support for dictator policies? We study this question in the context of Germany before World War II, between 1929 and 1939. First, we estimate the impact of radio signal on voting for the Nazi party before and after Nazi got control over the content of the broadcast. Prior to Hitler s appointment as chancellor, the radio, broadcasting cultural programs and some political news with an anti-Nazi slant, had a substantial negative effect on voting for the Nazi party. This negative effect was fully undone in just one month before the last competitive pre-war election following Hitler s appointment in 1933, which resulted in the change of radio content to heavy pro-Nazi propaganda. In the last few months that Germany remained democracy, the persuasion power of pro-Nazi propaganda was smaller than that of the anti-Nazi radio. Second, we examine the impact of the radio after Nazi fully consolidated power. Radio propaganda helped Nazi to enroll new party members and encouraged denunciations of Jews and other open expressions of anti-Semitism. Radio was most effective as propaganda tool when combined with other tools, such as Hitler s speeches, and when the message was more aligned with listeners priors as measured by historical variation in anti-Semitism.
Keywords: D72; L82; P26; 330